The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.bjm.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove endophyte promotes reforestation tree ( Acacia polyphylla ) growth

Abstract: Mangroves are ecosystems located in the transition zone between land and sea that serve as a potential source of biotechnological resources. Brazil's extensive coast contains one of the largest mangrove forests in the world (encompassing an area of 25,000 km2 along all the coast). Endophytic bacteria were isolated from the following three plant species: Rhizophora mangle, Laguncularia racemosa and Avicennia nitida. A large number of these isolates, 115 in total, were evaluated for their ability to fix nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 48 publications
(54 reference statements)
0
17
0
2
Order By: Relevance
“…The role of endophytes in forest communities remains poorly understood; however, high-throughput technologies have increased the speed and resolution in screening microbial communities (Hardoim et al, 2015; Baldrian, 2017). Endophyte inoculated trees have shown: (1) positive growth trends (Chanway and Holl, 1991; Chanway et al, 1994; Shishido et al, 1999; Khan et al, 2015; Castro et al, 2017), (2) adaptive phenotypic changes (Knoth et al, 2014; Vivas et al, 2015), (3) stress mitigation (Khan et al, 2016; Doty, 2017; Doty et al, 2017; Rho et al, 2018a, b), (4) nitrogen fixation (Anand and Chanway, 2013; Anand et al, 2013; Knoth et al, 2014), and (5) reduced damage from insect herbivores and fungal pathogens (Brooks et al, 1994; Miller, 2011; Pirttilä and Frank, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The role of endophytes in forest communities remains poorly understood; however, high-throughput technologies have increased the speed and resolution in screening microbial communities (Hardoim et al, 2015; Baldrian, 2017). Endophyte inoculated trees have shown: (1) positive growth trends (Chanway and Holl, 1991; Chanway et al, 1994; Shishido et al, 1999; Khan et al, 2015; Castro et al, 2017), (2) adaptive phenotypic changes (Knoth et al, 2014; Vivas et al, 2015), (3) stress mitigation (Khan et al, 2016; Doty, 2017; Doty et al, 2017; Rho et al, 2018a, b), (4) nitrogen fixation (Anand and Chanway, 2013; Anand et al, 2013; Knoth et al, 2014), and (5) reduced damage from insect herbivores and fungal pathogens (Brooks et al, 1994; Miller, 2011; Pirttilä and Frank, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of the endophytic and rhizospheric bacteria diversity associated with J. curcas found the phyla Actinobacteria, Acidobacteria, Chlroflexi, Firmicutes, and Verrucomicrobia Annapurna;Saraf, 2012;Dubey et al 2016;Madhaiyan et al, 2012;Qin et al, 2015); which demonstrates the ability of the phyla found in the present study in Annapurna;Saraf, 2012;Madhaiyan et al, 2012;Madhaiyan et al, 2013). These genera have already been described as capable of promoting plant growth in various other crops (Chauhan, Bagyaraj, Sharma, 2013;Castro et al, 2017;Batista et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…This was attributed to the specifications of the TLS they used, the Faro Focus 120 3D phase‐shift TLS, and also the structural attributes of the study site. The Faro Focus 120 3D phase‐shift TLS provides much denser data when compared to the CBL, being able to collect up to 976,000 points per scan (Castro et al, 2018), while the CBL collects up to approximately 300,000 points per scan in natural environments. In addition, the beam divergence in the Faro Focus 120 3D is 0.19 mrad, which provides a higher resolution compared to the 15‐mrad beam divergence of the CBL, while the range accuracy for the Faro Focus 120 3D is as low as 2 mm (at ranges < 120 m), while the range accuracy for the CBL is specified as 30 mm (at ranges < 50 m) (Kelbe et al 2015).…”
Section: Discussionmentioning
confidence: 99%